2016
DOI: 10.1016/j.aei.2016.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Rapid data quality oriented laser scan planning for dynamic construction environments

Abstract: In construction environments, laser-scanning technologies can perform rapid spatial data collection to monitor construction progress, control construction quality, and support decisions about how to streamline field activities. However, even experienced surveyors cannot guarantee comprehensive laser scanning data collection in the field due to its constantly changing environment, wherein a large number of objects are subject to different data-quality requirements. The current practice of manually planned laser… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(44 citation statements)
references
References 45 publications
0
44
0
Order By: Relevance
“…It then selects sensing locations and plans the "minimum-time" path for moving the scanner to this location. Some studies have shown that the laser-scan planning problem can be solved using as-designed models [11], [12]. However, current practices still manually collect and process the 3D point clouds of large-scale environments, which requires many scans and often results in high labor and time costs, human errors, and inconsistent data quality.…”
Section: Scan Planning and Autonomous Scanningmentioning
confidence: 99%
“…It then selects sensing locations and plans the "minimum-time" path for moving the scanner to this location. Some studies have shown that the laser-scan planning problem can be solved using as-designed models [11], [12]. However, current practices still manually collect and process the 3D point clouds of large-scale environments, which requires many scans and often results in high labor and time costs, human errors, and inconsistent data quality.…”
Section: Scan Planning and Autonomous Scanningmentioning
confidence: 99%
“…The viewpoint resampling was employed to design customized inspection routes that maximize the coverage and completeness of constructed 3D models for existing structures (Bircher et al 2016). While tailored to terrestrial laser scanning, scan stations were automatically identified while taking into account the accuracy and the level of detail of the resulting 3D point clouds of target structures (Zhang et al 2016). Another study further elaborated on the interoperable and IFC-based integration of UAV mission planning modules with progress tracking and automated as-built modeling solutions (Hamledari 2017)…”
Section: Related Workmentioning
confidence: 99%
“…To increase the accuracy of such vision-based techniques, it is crucial to investigate the design of UAV image acquisition strategies that ensure the high quality of captured data (Morgenthal and Hallermann 2014). The data captured during manually planned inspections suffers from detail, coverage, and accuracy (Zhang et al 2016); the construction dynamics and changes in the building layouts also increase the need for model-driven and automatic planning of UAV inspection missions.…”
Section: Introductionmentioning
confidence: 99%
“…The latter, which can be collected using any type of 3D scanner, have become increasingly affordable and thus popular in recent years (Tang et al, 2010;Wang et al, 2017). Considerable advances have also been made in point cloud preparation and pre-processing proficiencies (e.g., Song et al, 2014;Zhang et al, 2016) in model generation methods (e.g., Bosché et al, 2015;Díaz-Vilariño et al, 2015) and for semantic enrichment (Belsky et al, 2016;Hamledari et al, 2017;Sacks et al, 2017). For example, by cloaking the geometry of an existing facility as meshes, a model can mimic the real-life object and its exterior and interior surfaces with millimeter accuracy.…”
Section: Introductionmentioning
confidence: 99%